(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2012)
This study was conducted to evaluate the potential induction of genotoxic effects of white bean flour using the Comet assay. The test was conducted with human lymphocytes present in whole blood immediately after collection, by incubation with white bean flour in three concentrations (3.92, 9.52 and 18.18 mg/mL) at 37 ºC for 4 h followed by preparation of slides. Samples were considered positive (above 20% damage) when the damage observed to cellular DNA was higher than the negative control. No genotoxic potential was found at the doses tested. However, it would be premature to suggest absence of risk to human health of DNA damage since the exposure of cells to the extract was restricted to four hours rather than a whole cell cycle. Additionally, further information on toxicology should be obtained in future studies.